A preparation method of Litsea cubeba essential oil microcapsules
By modifying microcrystalline cellulose and crosslinking with oxidized hyaluronic acid, combined with secondary crosslinking of epoxy soybean oil, the problems of low embedding rate of Shancangzi essential oil and unstable sustained release performance are solved. It achieves high embedding rate and stable sustained release performance, especially in ultraviolet radiation environments.
Patent Information
- Application Number
- CN202411578008.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing Shancangzi essential oil microcapsules have low embedding rate, unstable sustained release performance, and poor UV radiation resistance, which limits its use range.
A specific method is used to modify the microcrystalline cellulose twice, and the cross-linking reaction between oxidized hyaluronic acid and modified microcrystalline cellulose is coated with shancrystalline essential oil in a cross-linked network structure, and finally through the ring Secondary cross-linking of oxygen soybean oil improves embedding rate and sustained release performance, and enhances UV radiation resistance.
Improve the embedding rate of Shancangzi essential oil microcapsules to 86.6-87.1%, enhance the sustained release performance, especially in ultraviolet radiation environment, effectively protect essential oil components, and extend the service life of the product. .
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microcapsules, and particularly relates to a method for preparing litsea cubeba essential oil microcapsules. Background Art
[0002] Litsea cubeba essential oil is a natural essential oil extracted from fresh Litsea cubeba fruit. It is slightly yellow in color and contains the following main chemical components: citral, limonene, methyl heptenone, cilantro, geraniol, geranial, etc. Litsea cubeba essential oil has good antibacterial, anti-inflammatory and antioxidant properties. It is also beneficial for dredging meridians, improving rough and dry skin, and relieving fatigue. It is widely used in the fields of medicine, spices, cosmetics, etc. However, Litsea cubeba essential oil has a strong irritating odor, is sensitive to light, air, and temperature, is volatile, and is difficult to store for a long time, which greatly limits its scope of use.
[0003] Microencapsulation technology is a technology that uses natural or synthetic polymers as wall materials and small solids, liquids, and gases as core materials, and constructs micro-containers through emulsification, polymerization, complex coagulation and other means to encapsulate active ingredients. The elm litsea cubeba essential oil microcapsules use elm litsea cubeba essential oil as the core material and use polymer materials as wall materials to encapsulate it to form tiny particles, which can isolate the essential oil core material and avoid the influence of external factors such as light, air and temperature, thereby protecting the core material and reducing the volatility of elm litsea cubeba essential oil. Therefore, essential oil microencapsulation technology has become a current research hotspot, which has effectively solved the problems in the application of plant essential oils and expanded the development of the plant essential oil industry.
[0004] CN117839580A discloses a litsea cubeba essential oil microcapsule and its preparation method and application, and specifically discloses that water-soluble chitosan is used as a single wall material and litsea cubeba essential oil is used as a core material, and litsea cubeba essential oil microcapsules are successfully prepared by a spray drying method;
[0005] The raw materials of this method are easy to obtain, low in cost, more easily degraded in the body, more types of essential oil active ingredients can be embedded, and the water solubility is better, but the embedding rate is low and the release rate is unstable.
[0006] CN115069180A discloses a secondary cross-linked plant essential oil microcapsule and its preparation method and application. Specifically, it discloses that aldehyde-modified soybean polysaccharide and ε-polylysine are used as composite wall materials, and then glutaraldehyde is introduced to perform secondary cross-linking on the composite system, which effectively reduces the volatility of the plant essential oil, improves the stability of the plant essential oil, and enhances the sustained release and antibacterial effects.
[0007] The essential oil microcapsules produced by this patent have an embedding rate of 78.3% and a release rate of 20% after being placed at room temperature for 60 days. The release rate at room temperature is stable, but its embedding rate is still low, and the release rate in an ultraviolet environment increases sharply. The sustained-release performance is unstable, which greatly limits the scope of use. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing Litsea cubeba essential oil microcapsules, which have high embedding rate, stable sustained-release performance and good ultraviolet radiation resistance.
[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0010] 1. Preparation of modified microcrystalline cellulose
[0011] (1) Primary modification
[0012] The microcrystalline cellulose is placed in an ethanol solution, polyethylene glycol 600 is added and stirred at a temperature of 37-42° C. for 2.7-3.2 hours. After the stirring is completed, monoethanolamine and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane are added, the temperature is raised to 70-74° C., and the reaction is stirred for 5.8-6.3 hours. After the reaction is completed, the solution is filtered, washed, and dried to obtain polyamino microcrystalline cellulose;
[0013] The mass ratio of microcrystalline cellulose, ethanol solution, polyethylene glycol 600, monoethanolamine and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 9.7-10.2:92-98:0.6-0.8:0.4-0.6:0.7-0.9;
[0014] The mass concentration of the ethanol solution is 30-34%;
[0015] (2) Secondary modification
[0016] N,N-dimethylformamide is introduced into a sealed reaction container, polylactic acid is added, and after stirring evenly, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and hydroxysuccinimide are added, and PBS buffer of 2-(N-morpholino)ethanesulfonic acid with a pH of 6.0-6.3 is added to adjust the pH to 5.5-5.7, and stirred for 32-38 minutes, and then polyamino microcrystalline cellulose is added, and ammonia water is added to adjust the pH to 7.1-7.5, and the reaction is stirred for 9.8-10.3 hours to obtain modified microcrystalline cellulose;
[0017] The volume mass ratio of the N,N-dimethylformamide, polylactic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, hydroxysuccinimide and polyamino microcrystalline cellulose is 380-410 mL: 3.1-3.5 g: 0.18-0.22 g: 0.11-0.13 g: 8.5-9.0 g;
[0018] The mass concentration of the ammonia water is 18-23%.
[0019] 2. Preliminary coating
[0020] Place oxidized hyaluronic acid in deionized water, stir evenly, add composite emulsifier and Litsea cubeba essential oil, stir at high speed, stirring at a speed of 2470-2530 rpm, stirring for 28-34 min, add modified microcrystalline cellulose after stirring, raise the temperature to 40-45° C., keep warm for 3.4-3.7 h, filter, wash and dry after reaction to obtain primary microcapsules;
[0021] The mass ratio of the oxidized hyaluronic acid, deionized water, composite emulsifier, Litsea cubeba essential oil and modified microcrystalline cellulose is 2.0-2.3:48-53:1.1-1.4:0.3-0.5:4.5-4.9;
[0022] The composite emulsifier is a mixture of ceteareth-25 and Tween 20, and the mass ratio of ceteareth-25 to Tween 20 is 0.6-0.8:1.5-1.8;
[0023] The preparation method of the oxidized hyaluronic acid comprises placing the hyaluronic acid in a hydrogen peroxide solution and stirring the hyaluronic acid at a temperature of 36-39° C. for a stirring time of 1.4-1.7 hours. After the stirring is completed, sodium periodate is added, and the temperature is raised to 40-45° C. at a rate of 0.4-0.6° C. / min, and the stirring reaction is performed for 1.8-2.2 hours. After the reaction is completed, the hyaluronic acid is dialyzed and placed at -37 to -34° C. for freeze drying for 11-13 hours to obtain the oxidized hyaluronic acid.
[0024] The mass ratio of the hyaluronic acid, hydrogen peroxide solution and sodium periodate is 6.7-7.2:72-76:6.8-7.2;
[0025] The mass concentration of the hydrogen peroxide solution is 28-32%.
[0026] 3. Secondary cross-linking
[0027] The primary microcapsules are placed in deionized water, epoxy soybean oil is added, and after stirring evenly, chitosan solution is slowly added, and the addition rate of the chitosan solution is controlled to be 3.8-4.2 mL / min. After the addition is completed, the mixture is stirred at 290-310 rpm for 18-22 min, and the temperature is raised to 51-55° C. at a rate of 0.8-1.2° C. / min, and the reaction is kept warm for 0.8-1.2 h. After the reaction is completed, the mixture is filtered and washed, first dried at -22 to -18° C. for 5.8-6.3 h, and then dried at -32 to -28° C. for 5.7-6.4 h. After the drying is completed, the mixture is naturally restored to room temperature to obtain litsea cubeba essential oil microcapsules;
[0028] The mass volume ratio of the primary microcapsules, deionized water, epoxidized soybean oil, and chitosan solution is 7.5-8.0 g: 28-32 g: 1.8-2.3 g: 57-63 mL;
[0029] The chitosan solution is a mixture of chitosan and 3.3-3.7wt% acetic acid, and the mass ratio of the chitosan to the 3.3-3.7wt% acetic acid is 1.5-1.7:50.
[0030] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0031] 1. The present invention adopts a specific method to modify microcrystalline cellulose twice. The primary modification is to disperse the microcrystalline cellulose to improve the surface dispersion performance, and then introduce amino groups. In the secondary modification step, polylactic acid is introduced. Through the amidation reaction of polylactic acid and polyamino microcrystalline cellulose, modified microcrystalline cellulose with good dispersion performance and excellent stability is obtained, and a reaction site is provided for the subsequent secondary cross-linking. In the preliminary coating process, the oxidized hyaluronic acid and the modified microcrystalline cellulose are cross-linked to coat the litsea cubeba essential oil, so that the litsea cubeba essential oil is firmly coated in the cross-linked network structure, the volatilization of the essential oil is reduced, the stability of the essential oil is improved, and the sustained-release performance is enhanced. Finally, epoxy soybean oil is used as a cross-linking agent to perform secondary cross-linking on the primary microcapsules and chitosan, which increases the embedding rate of the essential oil, further increases the stability of the microcapsules, and makes the sustained-release performance excellent. The ultraviolet irradiation environment has little effect on the sustained-release performance, the sustained-release stability is good, and the essential oil components inside the microcapsules are effectively protected, thereby improving the long-term use performance of the microcapsule product.
[0032] 2. The embedding rate of the Litsea cubeba essential oil microcapsules prepared by the method of the present invention is 86.6-87.1%;
[0033] 3. The essential oil microcapsules of Litsea cubeba essential oil prepared by the method of the present invention are placed in an environment with a temperature of 26° C. and a humidity of 70%. The essential oil release rate after standing for 10 days is 6.4-6.8%, the essential oil release rate after standing for 30 days is 10.1-10.9%, the essential oil release rate after standing for 60 days is 18.9-19.6%, the essential oil release rate after standing for 120 days is 44.2-45.5%, and the essential oil release rate after standing for 180 days is 74.5-75.8%;
[0034] 4. The Litsea cubeba essential oil microcapsules prepared by the method of the present invention are 2 After standing under ultraviolet light for 10 days, the essential oil release rate was 7.0-7.5%, and the essential oil release rate after standing for 15 days was 10.7-11.6%. DETAILED DESCRIPTION
[0035] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0036] Example 1
[0037] 1. Preparation of modified microcrystalline cellulose
[0038] (1) Primary modification
[0039] 10.0 g of microcrystalline cellulose was placed in 95 g of 32 wt% ethanol solution, 0.7 g of polyethylene glycol 600 was added and stirred at 40° C. for 3.0 h. After the stirring, 0.5 g of monoethanolamine and 0.8 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane were added, the temperature was raised to 72° C., and the reaction was stirred for 6.0 h. After the reaction was completed, the solution was filtered, washed, and dried to obtain polyamino microcrystalline cellulose;
[0040] (2) Secondary modification
[0041] 400 mL of N,N-dimethylformamide was introduced into a sealed reaction vessel, 3.3 g of polylactic acid was added, and after stirring evenly, 0.20 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.12 g of hydroxysuccinimide were added, and PBS buffer of 2-(N-morpholino)ethanesulfonic acid with a pH of 6.2 was added to adjust the pH to 5.6, stirred for 35 min, and then 8.7 g of polyamino microcrystalline cellulose was added, and 20 wt % ammonia water was added to adjust the pH to 7.3, and the reaction was stirred for 10 h to obtain modified microcrystalline cellulose.
[0042] 2. Preliminary coating
[0043] 2.1 g of oxidized hyaluronic acid was placed in 50 g of deionized water, and after stirring evenly, 1.3 g of composite emulsifier and 0.4 g of Litsea cubeba essential oil were added, and high-speed stirring was performed at a stirring speed of 2500 rpm for 30 min. After the stirring was completed, 4.7 g of modified microcrystalline cellulose was added, and the temperature was raised to 42° C. and the reaction was kept warm for 3.5 h. After the reaction was completed, the primary microcapsules were obtained after filtering, washing and drying;
[0044] The composite emulsifier is a mixture of ceteareth-25 and Tween 20, and the mass ratio of ceteareth-25 to Tween 20 is 0.7:1.6;
[0045] The preparation method of the oxidized hyaluronic acid is as follows: 7.0 g of hyaluronic acid is placed in 74 g of a 30 wt% hydrogen peroxide solution, and stirred at 37° C. for 1.5 h. After the stirring, 7.0 g of sodium periodate is added, and the temperature is raised to 42° C. at a rate of 0.5° C. / min, and the reaction is stirred for 2.0 h. After the reaction is completed, after dialysis, the solution is placed at -36° C. for freeze drying for 12 h to obtain the oxidized hyaluronic acid.
[0046] 3. Secondary cross-linking
[0047] 7.8g of primary microcapsules were placed in 30g of deionized water, 2.0g of epoxy soybean oil was added, and after stirring evenly, 60mL of chitosan solution was slowly added, and the addition rate of the chitosan solution was controlled to be 4.0mL / min. After the addition was completed, the mixture was stirred at 300rpm for 20min, and the temperature was raised to 53°C at a rate of 1.0°C / min. The mixture was kept warm for 1.0h. After the reaction was completed, the mixture was filtered and washed, and dried at -20°C for 6.0h, and then dried at -30°C for 6.0h. After the drying was completed, the mixture was naturally restored to room temperature to obtain Litsea cubeba essential oil microcapsules;
[0048] The chitosan solution is a mixture of chitosan and 3.5 wt % acetic acid, and the mass ratio of the chitosan to the 3.5 wt % acetic acid is 1.6:50.
[0049] Example 2
[0050] 1. Preparation of modified microcrystalline cellulose
[0051] (1) Primary modification
[0052] 9.7 g of microcrystalline cellulose was placed in 92 g of 30 wt% ethanol solution, 0.6 g of polyethylene glycol 600 was added and stirred at 37° C. for 2.7 h. After the stirring, 0.4 g of monoethanolamine and 0.7 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane were added, the temperature was raised to 70° C., and the reaction was stirred for 6.3 h. After the reaction was completed, the solution was filtered, washed, and dried to obtain polyamino microcrystalline cellulose;
[0053] (2) Secondary modification
[0054] 380 mL of N,N-dimethylformamide was introduced into a sealed reaction vessel, 3.1 g of polylactic acid was added, and after stirring evenly, 0.18 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.11 g of hydroxysuccinimide were added, and PBS buffer of 2-(N-morpholino)ethanesulfonic acid with a pH of 6.0 was added to adjust the pH to 5.5, stirred for 32 min, and then 8.5 g of polyamino microcrystalline cellulose was added, and 18 wt % ammonia water was added to adjust the pH to 7.1, and the reaction was stirred for 9.8 h to obtain modified microcrystalline cellulose.
[0055] 2. Preliminary coating
[0056] 2.0 g of oxidized hyaluronic acid was placed in 48 g of deionized water, and after stirring evenly, 1.1 g of composite emulsifier and 0.3 g of Litsea cubeba essential oil were added, and high-speed stirring was performed at a stirring speed of 2470 rpm for 34 min. After the stirring was completed, 4.5 g of modified microcrystalline cellulose was added, and the temperature was raised to 40° C. and the reaction was kept warm for 3.4 h. After the reaction was completed, the primary microcapsules were obtained after filtering, washing and drying;
[0057] The composite emulsifier is a mixture of ceteareth-25 and Tween 20, and the mass ratio of ceteareth-25 to Tween 20 is 0.6:1.5;
[0058] The preparation method of the oxidized hyaluronic acid is as follows: 6.7 g of hyaluronic acid is placed in 72 g of a 28 wt% hydrogen peroxide solution, and stirred at a temperature of 36° C. for 1.7 hours. After the stirring, 6.8 g of sodium periodate is added, and the temperature is raised to 40° C. at a rate of 0.4° C. / min, and the reaction is stirred for 1.8 hours. After the reaction is completed, the hyaluronic acid is dialyzed and placed at -34° C. for freeze drying for 13 hours to obtain the oxidized hyaluronic acid.
[0059] 3. Secondary cross-linking
[0060] 7.5 g of primary microcapsules were placed in 28 g of deionized water, 1.8 g of epoxy soybean oil was added, and after stirring evenly, 57 mL of chitosan solution was slowly added, and the addition rate of the chitosan solution was controlled to be 3.8 mL / min. After the addition was completed, the mixture was stirred at 290 rpm for 18 min, and the temperature was raised to 51°C at a rate of 0.8°C / min, and the reaction was kept warm for 0.8 h. After the reaction was completed, the mixture was filtered and washed, first dried at -22°C for 5.8 h, and then dried at -32°C for 5.7 h. After the drying was completed, the mixture was naturally restored to room temperature to obtain Litsea cubeba essential oil microcapsules;
[0061] The chitosan solution is a mixture of chitosan and 3.3 wt % acetic acid, and the mass ratio of the chitosan to the 3.3 wt % acetic acid is 1.5:50.
[0062] Example 3
[0063] 1. Preparation of modified microcrystalline cellulose
[0064] (1) Primary modification
[0065] 10.2 g of microcrystalline cellulose was placed in 98 g of 34 wt% ethanol solution, and 0.8 g of polyethylene glycol 600 was added and stirred at 42 ° C for 3.2 h. After the stirring, 0.6 g of monoethanolamine and 0.9 g of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane were added, and the temperature was raised to 74 ° C. The reaction was stirred for 5.8 h. After the reaction was completed, the solution was filtered, washed and dried to obtain polyamino microcrystalline cellulose;
[0066] (2) Secondary modification
[0067] 410 mL of N,N-dimethylformamide was introduced into a sealed reaction vessel, 3.5 g of polylactic acid was added, and after stirring evenly, 0.22 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.13 g of hydroxysuccinimide were added, and PBS buffer of 2-(N-morpholino)ethanesulfonic acid with a pH of 6.3 was added to adjust the pH to 5.7, stirred for 38 min, and then 9.0 g of polyamino microcrystalline cellulose was added, and 23 wt % ammonia water was added to adjust the pH to 7.5, and the reaction was stirred for 10.38 h to obtain modified microcrystalline cellulose.
[0068] 2. Preliminary coating
[0069] 2.3 g of oxidized hyaluronic acid was placed in 5348 g of deionized water, and after stirring evenly, 1.4 g of composite emulsifier and 0.5 g of Litsea cubeba essential oil were added, and high-speed stirring was performed at a stirring speed of 2530 rpm for 28 min. After the stirring was completed, 4.9 g of modified microcrystalline cellulose was added, and the temperature was raised to 45° C. and the reaction was kept warm for 3.7 h. After the reaction was completed, the primary microcapsules were obtained after filtering, washing and drying;
[0070] The composite emulsifier is a mixture of ceteareth-25 and Tween 20, and the mass ratio of ceteareth-25 to Tween 20 is 0.8:1.8;
[0071] The preparation method of the oxidized hyaluronic acid is as follows: 7.2 g of hyaluronic acid is placed in 76 g of a 32 wt% hydrogen peroxide solution, and stirred at a temperature of 39° C. for 1.4 h. After the stirring, 7.2 g of sodium periodate is added, and the temperature is raised to 45° C. at a rate of 0.6° C. / min, and the reaction is stirred for 2.2 h. After the reaction is completed, after dialysis, the hyaluronic acid is placed at -374° C. for freeze drying for 11 h to obtain the oxidized hyaluronic acid.
[0072] 3. Secondary cross-linking
[0073] 8.0g of primary microcapsules were placed in 32g of deionized water, 2.3g of epoxy soybean oil was added, and after stirring evenly, 63mL of chitosan solution was slowly added, and the addition rate of the chitosan solution was controlled to be 4.2mL / min. After the addition was completed, the mixture was stirred at 310rpm for 22min, and the temperature was raised to 55°C at a rate of 1.2°C / min. The mixture was kept warm for 1.2h. After the reaction was completed, the mixture was filtered and washed, first dried at -18°C for 6.3h, and then dried at -28°C for 6.4h. After drying, the mixture was naturally restored to room temperature to obtain Litsea cubeba essential oil microcapsules;
[0074] The chitosan solution is a mixture of chitosan and 3.7 wt % acetic acid, and the mass ratio of the chitosan to the 3.7 wt % acetic acid is 1.7:50.
[0075] Comparative Example 1
[0076] Based on Example 1, the changes are as follows:
[0077] In the step of modifying microcrystalline cellulose, the secondary modification step is omitted; in the primary coating step, an equal amount of modified microcrystalline cellulose is replaced by polyamino microcrystalline cellulose;
[0078] In the preliminary coating step, the oxidized hyaluronic acid component was omitted and an equal amount of the oxidized hyaluronic acid was replaced with deionized water;
[0079] The rest of the operations are the same.
[0080] Comparative Example 2
[0081] Based on Example 1, the changes are as follows:
[0082] The secondary cross-linking step is omitted, and the obtained primary microcapsules are litsea cubeba essential oil microcapsules;
[0083] The rest of the operations are the same.
[0084] Performance Testing
[0085] 1. Embedding rate
[0086] The embedding rate of the Litsea cubeba essential oil microcapsule products obtained in Example 1-3 and Comparative Example 1-2 was determined. The specific determination method was to take 1.0 g of the Litsea cubeba essential oil microcapsule products obtained in Example 1-3 and Comparative Example 1-2, respectively, rinse with 95 wt % ethanol solution, take the filtrate and measure its absorbance to obtain the content of Litsea cubeba essential oil that was not embedded;
[0087] Then, 1.0 g of the Litsea cubeba essential oil microcapsule products obtained in Examples 1-3 and Comparative Examples 1-2 were taken respectively, added to 500 mL of 95 wt % ethanol solution for ultrasonic treatment, the ultrasonic time was 10 min, the ultrasonic power was 600 W, and the ultrasonic frequency was 30 kHz. After the ultrasonic treatment, the mixture was stirred at 350 rpm for 2.0 h until the oil was completely extracted from the capsules, the insoluble matter in the mixed solution was removed by filtration, and the absorbance of the solution was measured by a spectrophotometer to obtain the total oil content in the microcapsule product;
[0088] The embedding rate was calculated and the result was the average of three parallel tests, where embedding rate % = (total oil content in the microcapsule product - content of unembedded Litsea cubeba essential oil) / original amount of essential oil added × 100%;
[0089] The calculation results are as follows:
[0090]
[0091] 2. Sustained release performance
[0092] The litsea cubeba essential oil microcapsule products prepared in Examples 1-3 and Comparative Examples 1-2 were respectively taken, and the total oil content in the microcapsules before standing was tested, and then placed in an environment with a temperature of 26° C. and a humidity of 70% for standing for 10 d, 30 d, 60 d, 120 d, and 180 d, respectively. After the standing was completed, the total oil content in the microcapsules after standing was tested;
[0093] The essential oil release rate of the microcapsule was calculated and the result was the average of three parallel tests, where the essential oil release rate = (total oil amount in the microcapsule before standing - total oil amount in the microcapsule after standing) / total oil amount in the microcapsule before standing; the calculation results are as follows:
[0094]
[0095] 3. Ultraviolet radiation resistance
[0096] Take the Litsea cubeba essential oil microcapsule products prepared in Examples 1-3 and Comparative Examples 1-2 respectively, test the total oil content in the microcapsule before standing, and then test the total oil content in the microcapsule under an intensity of 470 W / cm 2The microcapsules were placed under ultraviolet light for 10 days and 15 days, and the total oil content in the microcapsules was tested after the standing time.
[0097] The essential oil release rate of the microcapsule was calculated and the result was the average of three parallel tests, where the essential oil release rate = (total oil amount in the microcapsule before standing - total oil amount in the microcapsule after standing) / total oil amount in the microcapsule before standing; the calculation results are as follows:
[0098]
[0099] The invention adopts a specific method to modify the microcrystalline cellulose twice. The primary modification is to disperse the microcrystalline cellulose to improve the surface dispersion performance, and then introduce amino groups. In the secondary modification step, polylactic acid is introduced. Through the amidation reaction of polylactic acid and polyamino microcrystalline cellulose, modified microcrystalline cellulose with good dispersion performance and excellent stability is obtained, and reaction sites are provided for subsequent secondary cross-linking. In the initial coating process, the oxidized hyaluronic acid and the modified microcrystalline cellulose are cross-linked to coat the lilacinus litsea cubeba essential oil, so that the lilacinus litsea cubeba essential oil is stably coated in the cross-linked network structure, the volatilization of the essential oil is reduced, the stability of the essential oil is improved, and the sustained-release performance is enhanced. Finally, epoxy soybean oil is used as a cross-linking agent to perform secondary cross-linking on the primary microcapsule and chitosan, so as to increase the embedding rate of the essential oil, further increase the stability of the microcapsule, make the sustained-release performance excellent, and the ultraviolet irradiation environment has little influence on the sustained-release performance, the sustained-release stability is good, and the essential oil components inside the microcapsule are effectively protected, thereby improving the long-term use performance of the microcapsule product.
[0100] In Comparative Example 1, the secondary modification step of microcrystalline cellulose is omitted, and polyamino microcrystalline cellulose is directly used for preliminary coating. The oxidized hyaluronic acid component is also omitted. The polyamino microcrystalline cellulose directly coats the essential oil, and the embedding rate is low, which affects the sustained-release performance of the essential oil. In addition, in the preliminary coating step, intermolecular cross-linking cannot be effectively achieved, and the reaction sites in the secondary cross-linking step are reduced, which ultimately affects the sustained-release stability performance, shortens the service life of the microcapsule product, and greatly limits the product application.
[0101] In Comparative Example 2, the secondary cross-linking step is omitted, and the primary microcapsules obtained are the Litsea cubeba essential oil microcapsule products. The primary microcapsules have a low embedding rate and a low degree of intermolecular cross-linking, which affects the sustained-release effect of the product. In addition, the stability is poor and the product is greatly affected by the external environment, which reduces the application scope of the microcapsules.
[0102] Unless otherwise specified, all percentages used in the present invention are by mass.
[0103] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing Litsea cubeba essential oil microcapsules, characterized in that: The method comprises the steps of preparing modified microcrystalline cellulose, primary coating and secondary cross-linking; The preparation of modified microcrystalline cellulose includes primary modification and secondary modification; The secondary modification step is to introduce N,N-dimethylformamide into a closed reaction container, add polylactic acid, stir evenly, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and hydroxysuccinimide, add PBS buffer of 2-(N-morpholino)ethanesulfonic acid with a pH of 6.0-6.3 to adjust the pH to 5.5-5.7, stir for 32-38 minutes, then add polyamino microcrystalline cellulose, add ammonia water to adjust the pH to 7.1-7.5, stir and react for 9.8-10.3 hours to obtain modified microcrystalline cellulose; The preliminary coating step is to place oxidized hyaluronic acid in deionized water, stir evenly, add composite emulsifier and Litsea cubeba essential oil, stir at high speed, the stirring speed is 2470-2530rpm, the stirring time is 28-34min, after the stirring is completed, add modified microcrystalline cellulose, increase the temperature to 40-45°C, keep warm for reaction for 3.4-3.7h, after the reaction is completed, filter, wash and dry to obtain primary microcapsules; The secondary cross-linking step comprises placing the primary microcapsules in deionized water, adding epoxy soybean oil, stirring evenly, slowly adding chitosan solution, controlling the adding rate of the chitosan solution to be 3.8-4.2 mL / min, stirring at 290-310 rpm for 18-22 min, heating to 51-55° C. at a rate of 0.8-1.2° C. / min, and keeping the temperature for reaction for 0.8-1.2 h. After the reaction is completed, filtering and washing are performed and freeze-drying is performed. After drying is completed, the temperature is naturally restored to room temperature to obtain the litsea cubeba essential oil microcapsules.
2. The method for preparing a Litsea cubeba essential oil microcapsule according to claim 1, characterized in that: The primary modification step is to place microcrystalline cellulose in an ethanol solution, add polyethylene glycol 600 and stir, the stirring temperature is 37-42° C., the stirring time is 2.7-3.2 hours, after the stirring is completed, monoethanolamine and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane are added, the temperature is increased to 70-74° C., and the stirring reaction is carried out for 5.8-6.3 hours. After the reaction is completed, the polyamino microcrystalline cellulose is obtained by filtering, washing and drying.
3. The method for preparing a litsea cubeba essential oil microcapsule according to claim 2, characterized in that: In the primary modification step, the mass ratio of the microcrystalline cellulose, the ethanol solution, the polyethylene glycol 600, the monoethanolamine and the N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 9.7-10.2:92-98:0.6-0.8:0.4-0.6:0.7-0.9; The mass concentration of the ethanol solution is 30-34%.
4. The method for preparing a Litsea cubeba essential oil microcapsule according to claim 1, characterized in that: In the secondary modification step, the volume mass ratio of the N,N-dimethylformamide, polylactic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, hydroxysuccinimide and polyamino microcrystalline cellulose is 380-410 mL: 3.1-3.5 g: 0.18-0.22 g: 0.11-0.13 g: 8.5-9.0 g; The mass concentration of the ammonia water is 18-23%.
5. The method for preparing a litsea cubeba essential oil microcapsule according to claim 1, characterized in that: In the preliminary coating step, the mass ratio of the oxidized hyaluronic acid, deionized water, composite emulsifier, Litsea cubeba essential oil and modified microcrystalline cellulose is 2.0-2.3:48-53:1.1-1.4:0.3-0.5:4.5-4.9; The composite emulsifier is a mixture of ceteareth-25 and Tween 20, and the mass ratio of ceteareth-25 to Tween 20 is 0.6-0.8:1.5-1.
8.
6. The method for preparing a Litsea cubeba essential oil microcapsule according to claim 1, characterized in that: The preparation method of the oxidized hyaluronic acid comprises placing the hyaluronic acid in a hydrogen peroxide solution and stirring the hyaluronic acid at a temperature of 36-39° C. for a stirring time of 1.4-1.7 hours. After the stirring is completed, sodium periodate is added, and the temperature is raised to 40-45° C. at a rate of 0.4-0.6° C. / min, and the stirring reaction is performed for 1.8-2.2 hours. After the reaction is completed, the hyaluronic acid is dialyzed and placed at -37 to -34° C. for freeze drying for 11-13 hours to obtain the oxidized hyaluronic acid. The mass ratio of the hyaluronic acid, hydrogen peroxide solution and sodium periodate is 6.7-7.2:72-76:6.8-7.2; The mass concentration of the hydrogen peroxide solution is 28-32%.
7. The method for preparing a Litsea cubeba essential oil microcapsule according to claim 1, characterized in that: In the secondary cross-linking step, the freeze-drying is first carried out at -22 to -18°C for 5.8 to 6.3 hours, and then at -32 to -28°C for 5.7 to 6.4 hours.
8. The method for preparing a Litsea cubeba essential oil microcapsule according to claim 1, characterized in that: In the secondary cross-linking step, the mass volume ratio of the primary microcapsules, deionized water, epoxy soybean oil, and chitosan solution is 7.5-8.0 g: 28-32 g: 1.8-2.3 g: 57-63 mL; The chitosan solution is a mixture of chitosan and 3.3-3.7wt% acetic acid, and the mass ratio of the chitosan to the 3.3-3.7wt% acetic acid is 1.5-1.7:50.
Citation Information
Patent Citations
Litsea cubeba essential oil microcapsule as well as preparation method and application thereof
CN117839580A
Biodegradable polyurea / polyurethane microcapsules
CN116490265A
Healthcare buccal tablet for eliminating nodules and improving immunity and preparation method thereof
CN117717173A